EFFECT OF NECK MOBILIZATION AND NECK ISOMETRICS IN CERVICOGENIC HEADACHE. A RANDOMIZE CONTROLLED TRIAL (Journal of Medical & Health Sciences Review, 2025)
Cervicogenic headache (CGH) is a secondary headache resulting from cervical musculoskeletal dysfunction, involving muscles, joints, and nerves. Proper management is directed toward the restoration of cervical mobility, muscle tension reduction, and suppression of nerve irritation. The research compared the impacts of neck mobilization and neck isometric exercises in alleviating CGH symptoms. A randomized controlled trial was undertaken at Isra University, Islamabad Campus, and Social Security Hospital, Rawalpindi, involving 40 patients with CGH, randomly allocated into two groups of 20 each. A group received neck mobilizations, and the other did neck isometric exercises. Findings indicated that both interventions yielded notable improvements within groups. Headache Impact Test (HIT) identified significant decrease in headache intensity over time (p